Structural Performance Optimization of 3-Legged Self-Supporting Telecommunication Towers: A Comparative Study of Pipe, Angle, and Hybrid Sections with X, K-Up, and K-Down Bracing Configurations (Journal of Advances and Scholarly Researches in Allied Education, 2026)
With the explosive growth of wireless communication networks, structurally sound and energy efficient towers are in great demand. In this paper, the structural analysis of three-legged self-supporting telecom towers with three different section types (Angle, Pipe and Hybrid) and three different bracing schemes (X-Bracing, K-Up Bracing and K-Down Bracing) is compared. We used TNX Tower, a program based on the FEA approach, to model and evaluate towers with heights of 100 ft, 150 ft, & 200 ft. Conforming to the requirements of IS 875 Part 3:2015, IS 1893 Part-I:2016, & TIA-222-H, the investigation included Non-linear P-Delta effects to precisely assess the structural behavior under wind & seismic loading scenarios. Results for Base Shear, Maximum Horizontal Deflection, and Bending Moment were the main foci of the research. In terms of stiffness and deflection, pipe sections topped the list, whereas angle sections had the opposite effect, resulting in lower bending moments or base shear values. K-Down bracing was found to be more structurally efficient than X-bracing, in most cases, by reducing deflection, bending moment or base shear. The results indicated that the type of sections & type of bracing used would have an impact on the overall stability and performance of a telecommunication tower.